2015
DOI: 10.1016/j.watres.2015.06.025
|View full text |Cite
|
Sign up to set email alerts
|

In-situ activation of persulfate by iron filings and degradation of 1,4-dioxane

Abstract: Activation of persulfate by iron filings and subsequent degradation of 1,4-dioxane (dioxane) was studied in both batch-reactor and column systems to evaluate the potential of a persulfate-enhanced permeable reactive barrier (PRB) system for combined oxidative-reductive removal of organic contaminants from groundwater. In batch experiments, decomposition of persulfate to sulfate and degradation of dioxane both occurred rapidly in the presence of iron filings. Conversely, dioxane degradation by persulfate was co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
40
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 120 publications
(49 citation statements)
references
References 31 publications
3
40
1
Order By: Relevance
“…4B, the characteristic peaks of DMPO-OH adducts (with hyperfine splitting constants of a N ¼ a H ¼ 14.9 G) and DMPO-SO 4 adducts (with hyperfine splitting constants of a N ¼ 13.2 G, a H ¼ 9.6 G, a H ¼ 1.48 G and a H ¼ 0.78 G) were observed, revealing the simultaneous presence of both radicals. These results were consistent with some prior observations (Fang et al, 2013b;Zhong et al, 2015). By combination of the EPR analysis and the results of the classical quenching tests, it can be inferred that SO 4 À and OH participated in the PS oxidation of FLU collectively, while SO 4 À may have a larger contribution to the activation of PS by Fe 3 O 4 / MWCNTs/PHQ for FLU removal.…”
Section: Activation Mechanisms Of Ps With Fe 3 O 4 /Mwcnts/phqsupporting
confidence: 91%
“…4B, the characteristic peaks of DMPO-OH adducts (with hyperfine splitting constants of a N ¼ a H ¼ 14.9 G) and DMPO-SO 4 adducts (with hyperfine splitting constants of a N ¼ 13.2 G, a H ¼ 9.6 G, a H ¼ 1.48 G and a H ¼ 0.78 G) were observed, revealing the simultaneous presence of both radicals. These results were consistent with some prior observations (Fang et al, 2013b;Zhong et al, 2015). By combination of the EPR analysis and the results of the classical quenching tests, it can be inferred that SO 4 À and OH participated in the PS oxidation of FLU collectively, while SO 4 À may have a larger contribution to the activation of PS by Fe 3 O 4 / MWCNTs/PHQ for FLU removal.…”
Section: Activation Mechanisms Of Ps With Fe 3 O 4 /Mwcnts/phqsupporting
confidence: 91%
“…As an alternative to Fe 2+ , some researchers have switched to using zerovalent iron (Fe 0 ) as an activator for persulfate (Lee et al, 2010; Kambhu et al, 2012; Oh et al, 2010; Xiong et al, 2014; Zhong et al, 2015). Zerovalent iron has the advantage of being a solid that can serve as electron donor by itself as well as provide a longer term supply of Fe 2+ for persulfate activation.…”
Section: Introductionmentioning
confidence: 99%
“…Zerovalent iron has the advantage of being a solid that can serve as electron donor by itself as well as provide a longer term supply of Fe 2+ for persulfate activation. Zhong et al (2015) used iron-activated persulfate to treat dioxane and observed rapid decomposition during the first 30 min followed by a slower rate of decay. Kambhu et al (2012) and Chokejaroenrat et al (2015) also used Fe 0 to activate persulfate but did so by mixing persulfate and Fe 0 separately with wax to produce slow-release formulations (i.e., oxidant and iron candles).…”
Section: Introductionmentioning
confidence: 99%
“…For example, effective degradation was also reported for petroleum-hydrocarbons [20, 22] chlorinated ethylenes [24-26], chlorinated alkanes [27, 28], dioxane [29, 30], methyl tert-butyl ether (MTBE) [20, 31], polycyclic aromatic hydrocarbons (PAHs) [32-34]. Several studies have reported that persulfate was applied to remove COD and color, and improve biodegradability for landfill leachate in above-ground treatment systems.…”
Section: Introductionmentioning
confidence: 99%